GENERAL ANAESTHESIA VERSUS REGIONAL ANAESTHESIA FOR LUMBAR LAMINECTOMY: A REVIEW OF THE MODERN LITERATURE - Malik, Sara Haider; Saleem, Huma; Ashfaq, Allah Ditta; Malik, Ifrah Haider; Batool, Fizza; Siddique, Kashif (Journal of Ayub Medical College Abbottabad, 2020)
Background: Lumbar spine surgery can be performed using different anaesthetic techniques such as general endotracheal anaesthesia (GA) or spinal-based regional anaesthesia (RA). Few of the studies have been done to compare the outcomes of spinal anaesthesia versus general anaesthesia for lumbar laminectomies as both having some advantages as well as disadvantages but still it is controversial. The objective of current study is to make a comprehensive review of literature for comparing the outcomes of lumbar laminectomy performed under general anaesthesia versus spinal anaesthesia. Method: Literature search was performed by using PubMed, Google scholar and bibliography of related articles. To compare groups of general anaesthesia versus spinal anaesthesia, the variables focused were mean heart rate (HR), mean arterial pressure (MAP), blood loss during surgery, duration of surgery, post-operative anaesthesia care unit (PACU) time, post-operative narcotic use/pain scale, post-operative urinary retention, and post-operative nausea/vomiting. Results: Data of eleven studies were presented in current article, of these five were randomized controlled trials, three case-controls and four were retrospective cohort studies. 5/8 studies reported that SA group having more hemodynamic stability with postoperative outcomes as compared to GA. Likewise, majority of reviewed studies (7/8) reported better pain control or decreased requirement of analgesics in SA group. Additionally, more than half of the reviewed studies (5/8) reported lower incidence of postoperative nausea and vomiting among patients of SA group. Conclusion: The current study concluded that SA has better outcomes than GA in terms of hemodynamic stability and decrease postoperative adverse effects. So special attention should be paid for SA as an alternative to GA for lumbar laminectomy. Keywords: Spinal Anaesthesia; General Anaesthesia; Lumbar; Laminectomy